PROSEDUR PEMBUATAN RELAAS AKTA BERITA ACARA RAPAT UMUM PEMEGANG SAHAM (RUPS) PERSEROAN TERBATAS DENGAN MENGGUNAKAN MEDIA TELEKONFERENSI - Selamet Wahono (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTThe spread of COVID-19 that has occurred almost all over the world has had a major impact on various aspects, one of which is the holding of the General Meeting of Shareholders (GMS) by meeting face-to-face. In order to minimize the spread of COVID-19, holding the GMS by means of face-to-face meetings can be replaced with an online GMS through teleconference media. The notary's role is to make the Deed of Minutes of the GMS which is held online to ensure certainty, order and legal protection.The research method used is normative juridical by researching library materials using a statute approach.Based on the results of the research, the answers to the formulation of the problems put forward are: The procedure for making the Relaas of the Minutes of the General Meeting of Shareholders (GMS) of a Limited Liability Company using Teleconferencing Media is a Notary who acts in his position as a public official is present using Teleconferencing Media and makes a Deed of Minutes The GMS is based on what the Notary has seen and heard from the beginning until the end of the GMS. The legal basis for making the Relaas of the Minutes of the General Meeting of Shareholders (GMS) of a Limited Liability Company made by a Notary using Teleconferencing Media is the provisions of Article 15 paragraph (1) of the UUJN in conjunction with the provisions of Article 1868 of the Civil Code and the preparation of the Relaas of the Minutes of the GMS must comply with the following provisions: the provisions contained in the provisions of Article 38, Article 39, Article 40, and Article 44 of the UUJN. Keywords: Deed Relaas, GMS, Teleconference